2021
DOI: 10.3389/fdgth.2021.736418
|View full text |Cite
|
Sign up to set email alerts
|

Calibration-Free Gait Assessment by Foot-Worn Inertial Sensors

Abstract: Walking is a central activity of daily life, and there is an increasing demand for objective measurement-based gait assessment. In contrast to stationary systems, wearable inertial measurement units (IMUs) have the potential to enable non-restrictive and accurate gait assessment in daily life. We propose a set of algorithms that uses the measurements of two foot-worn IMUs to determine major spatiotemporal gait parameters that are essential for clinical gait assessment: durations of five gait phases for each si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 67 publications
3
19
0
Order By: Relevance
“…Gait events and phases were identified using the calibration-free gait assessment method introduced by [19]. The technique used angular rates and acceleration signals from two IMUs placed on the shoes and automatically adapted its parameters to the participant's gait velocity.…”
Section: Gait Temporal Characteristics-imc Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…Gait events and phases were identified using the calibration-free gait assessment method introduced by [19]. The technique used angular rates and acceleration signals from two IMUs placed on the shoes and automatically adapted its parameters to the participant's gait velocity.…”
Section: Gait Temporal Characteristics-imc Systemmentioning
confidence: 99%
“…It has been shown that the method can overcome the difficulty of identifying gait events in stroke patients' irregular gait patterns. Using the proposed method in [19], gait events-i.e., Initial Contacts (IC) and Final Contacts (FC)-were extracted from IMUs, which were placed on the shoes. The gait cycles began from the IC of one foot and lasted until the consecutive IC of the same foot.…”
Section: Gait Temporal Characteristics-imc Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…With increasing algorithm complexity, required processing resources rise yielding high energy consumption and waiting times between subsequent recordings. Still, algorithm development is an active area of research tackling these issues (e.g., Marín et al, 2020;Laidig et al, 2021). Also, existing hardware issues, such as limited recording time by battery and storage capacity, and data loss during the wireless transfer from sensors to applications or cloud servers should be a trivial problem in the future.…”
Section: Summary and Discussionmentioning
confidence: 99%